2016
DOI: 10.1136/injuryprev-2016-042218
|View full text |Cite
|
Sign up to set email alerts
|

The impact of child restraint legislation on the incidence of severe paediatric injury in Chile

Abstract: This is the first study to examine the association between CRL and severe paediatric injury in a Latin-American country. This study suggests that Chile's CRL was only effective in the short term. To support this type of reforms in the long term, other measures such as police enforcement, public information campaigns and involvement of public health professionals in educating parents about the benefits of using child restraints should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…First, the legislation explicitly differentiated between the devices required for each age group, thus reducing the risk of a technical mismatch. Notably, previous studies have stressed the importance of this distinction, warning that overly broad wording of the relevant laws may lead to such technical mismatches11 and will therefore be less effective 12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the legislation explicitly differentiated between the devices required for each age group, thus reducing the risk of a technical mismatch. Notably, previous studies have stressed the importance of this distinction, warning that overly broad wording of the relevant laws may lead to such technical mismatches11 and will therefore be less effective 12…”
Section: Discussionmentioning
confidence: 99%
“…Studies in North America and in Scandinavia have found that CRBLs lead to a reduction of between 10% and 22% in child injuries or fatalities 5–10. However, a study in Japan found no effect,11 and a study carried out in Chile found only a short-term effect 12. The cases of Japan and Chile are important because they suggest that both cultural elements and enforcement practices may be associated with the null or short-term impact of laws.…”
Section: Introductionmentioning
confidence: 98%
“…There is recent evidence suggesting that traffic fatality and injury rates among general and children populations in Chile may have been reduced by the introduction of the traffic law reform [5][6], and that large gains were observed when the enactment of the Chilean traffic law reform was followed by stronger police enforcement and supported by investments in road infrastructure, as it was demonstrated in the case of the general population [5]. However, research is lacking in such a vulnerable road user population as the older adults, which are differentially affected by chronic medical conditions and the use of medications [7][8], and agerelated performance declines in driving or street crossing behaviors [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the case of Chile, with an aging population, marked socioeconomic inequalities at the regional level, and important road safety measures implemented during the past decade, may be an interesting example for other developing nations. This is the first study to examine the geographical and temporal associations of road safety measures, socioeconomic inequalities, and road traffic deaths in the elderly, as previous studies have performed pooled analysis over several years [22] or geographical areas [5][6], conflating between-and within-regional processes (or time-dependent and time-independent effects). This study aimed to evaluate the impact of a set of road safety measures (the Chilean traffic law reform, the number of traffic offenses prosecuted in local police courts, and investment in road infrastructure), over the rate of road traffic deaths in older adults (60 years or older), considering the socioeconomic inequalities in the 13 regions of Chile over a period of 12 years (2002-2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is insufficient research on these factors cross-culturally and across demographics. Previous research has assessed the impact of macro level factors such as legislation on the use of child restraints (Brubacher et al, 2016;Nazif-Muñoz et al, 2017) and speculated on the macro level barriers to using a child restraint system e.g. the influence of appropriate use legislation and public policy (Brown et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%